Synthesis of New Organic Compounds Via Three Components Reaction with Studying of (Identification ,Thermal Behavior, Bioactivity on Bacteria of Teeth) - Nagham Mahmood Aljamali (Journal of Global Pharma Technology, 2018)
All  compounds  in  this  work  prepared  via  mannich   reaction   through  various  starting  materials  like  (  furan , thiophene ,  benzothiazole  derivatives  )  with   functional  groups  in   terminals  of  compounds  like ( hydroxyl  group , carboxyl  group ) ., our  method  involved  reaction  between  diamine  compounds   with  aromatic  aldehyde. then  identification  of  synthesized compounds  via  identification  techniques  ( FT.IR , H.NMR , Mass ) – spectrophotometric , studying  of  thermal   behavior   , studying  of  bioactivity  behavior  for  our  compounds  toward  types   of  bacteria  ( bacteria  of  Mouth like  ( Streptococcus  Mutans   ,   Streptococcus  Salivarius ) . Keywords: three components, bacteria, activity.